Why Do Nurses Fail to Implement Pain Assessment Instruments for Hospitalized Infants? - Azamolmolouk Elsagh; Abbas Ebadi; Asghar Dalvandi; Beheshteh Tabarsi (Iranian Journal of Nursing and Midwifery Research)
Background: Effective pain assessment in neonatal care is crucial for ensuring the well-being of newborns. However, barriers to its successful implementation persist. This study aims to identify the obstacles that hinder effective neonatal pain assessment by Neonatal Intensive Care Units (NICUs) nurses. Materials and Methods: This qualitative study was conducted using the method of conventional content analysis. Purposive sampling was employed from February to September 2023, selecting 14 female nurses working in NICUs of hospitals in Tehran and Karaj as participants. Indepth, semistructured interviews were conducted to collect the data. The software “MAXQDA” version 2016 was utilized for managing qualitative data. Results: Four main themes and eleven subthemes were identified: “Overtasked,” “Discordant atmosphere,” “Soulless care,” and “Lack of awareness.” Each of these main themes is further elaborated through the subsequent subthemes. Conclusions: This study found that the lack of knowledge and understanding of neonatal pain assessment tools, the busyness of nurses, lack of time, excessive documentation, and the inadequacy of staff relative to the number of newborns were the most significant obstacles to the assessment of newborn pain. Addressing these challenges is critical for optimal neonatal pain assessment and management, promoting the well-being of newborns.